2016
DOI: 10.1007/s00296-016-3583-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of clinical remission by treat to target strategy in established rheumatoid arthritis: results of the CREATE registry

Abstract: To analyse the cost-effectiveness, in daily clinical practice, of the strategy of treating to the target of clinical remission (CR) in patients with established rheumatoid arthritis (RA), after 2 years of treatment with biological therapy. Adult patients with established RA were treated with biological therapy and followed up for 2 years by a multidisciplinary team responsible for their clinical management. Treatment effectiveness was evaluated by the DAS28 score. The direct costs incurred during this period w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
1
0
4
Order By: Relevance
“…A registry study of patients with rheumatoid arthritis demonstrated that although a strategy of treating to a target of clinical remission was considered to be the most effective, direct costs to the health care service were rather high. 101 It is noteworthy that the study population had established disease and costs were accrued for up to 2 years; as discussed above, this may suggest that the window of opportunity for disease modification had been missed in these patients, and does not negate the possibility that a treat-to-target approach may be more effective over a longer period of time and when considering cost-effectiveness from a broader perspective.…”
Section: Discussionmentioning
confidence: 98%
“…A registry study of patients with rheumatoid arthritis demonstrated that although a strategy of treating to a target of clinical remission was considered to be the most effective, direct costs to the health care service were rather high. 101 It is noteworthy that the study population had established disease and costs were accrued for up to 2 years; as discussed above, this may suggest that the window of opportunity for disease modification had been missed in these patients, and does not negate the possibility that a treat-to-target approach may be more effective over a longer period of time and when considering cost-effectiveness from a broader perspective.…”
Section: Discussionmentioning
confidence: 98%
“…Es importante que en cada visita se realicen los ajustes terapéuticos necesarios en función de si se han conseguido los objetivos o no [85,125] . El objetivo es alcanzar la remisión o la baja actividad de la inflamación, con un tratamiento hacia el objetivo y un control adecuado y estricto de los pacientes, consiguiendo a su vez mejorar la relación entre el paciente y el profesional de reumatología.…”
Section: Situación Idealunclassified
“…El objetivo es alcanzar la remisión o la baja actividad de la inflamación, con un tratamiento hacia el objetivo y un control adecuado y estricto de los pacientes, consiguiendo a su vez mejorar la relación entre el paciente y el profesional de reumatología. Estudios previos sobre el uso de la estrategia T2T han demostrado claras ventajas en AR establecida [87,125] .…”
Section: Situación Idealunclassified
See 1 more Smart Citation
“…Die Kostenfrage von Therapiemodalitäten tritt zunehmend in den Vordergrund der Diskussionen und fließen in die Empfehlungen ein [3,6,[10][11][12][13][14][15]. Diese Notwendigkeit erschließt sich über die Zulassung v. a. hochpreisiger spezifischer Medikamentenentwicklungen der letzten zwei Jahrzehnte.…”
Section: Empfehlungen Und Leitlinienunclassified